Foreign Student Enrollment in the Czech Republic : A Comparative Push and Pull Analysis - Gonzalez, Benjamin Nathan (2024)
As international student numbers rise in the Czech Republic, the reasons for what draws them to the country is one of increasing importance. Economic indicators and statistical analyses of the available data on degree mobile students provide tremendous insight into the motivations leading to their pursuit of higher education abroad, which will be valuable as the country's demographics of the country shift and more young people and skilled workers are needed. This investigation delves into what areas the Czech Republic can look into to attract international students based on historical data, contemporary qualitative data, and existing literature in the global context as well as the local.